2009
DOI: 10.1002/hrm.20280
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of organizational efforts to lower turnover intentions: The moderating role of employee locus of control

Abstract: In the current career climate characterized by change and turbulence, employees may demonstrate limited psychological attachment to their employers. Rousseau (1998)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 83 publications
(100 reference statements)
2
49
1
3
Order By: Relevance
“…If performance reviews are completed on a regular basis, these reviews can help reinforce a sense of organizational membership for an employee, making them feel that the organization cares for them and wants them to perform well. As such, effective performance appraisals, by conveying care to the employee, can create a sense of reciprocity, leading to less voluntary turnover (Ng & Butts, 2009). …”
Section: Performance Appraisalmentioning
confidence: 99%
“…If performance reviews are completed on a regular basis, these reviews can help reinforce a sense of organizational membership for an employee, making them feel that the organization cares for them and wants them to perform well. As such, effective performance appraisals, by conveying care to the employee, can create a sense of reciprocity, leading to less voluntary turnover (Ng & Butts, 2009). …”
Section: Performance Appraisalmentioning
confidence: 99%
“…Some studies have proposed that employees with an ILC have stronger organizational commitment than those with an ELC (Coleman et al 1999;Furnham 1994;Kinicki and Vecchio 1994;Schyns and Collani 2002). Some researchers understand locus of control (ILC and ELC) as a moderator of the relationship between behaviors and work performance (Ng and Butts 2009;Norris and Niebuhr 1984;Srivastava 2009). …”
Section: The Moderating Role Of External Locus Of Controlmentioning
confidence: 94%
“…Mowday et al (1982) found that personality influenced individuals' affective commitments. Thus, locus of control has been introduced as a moderator to clarify the relationship between employees' behaviors and their work performances (Ng and Butts 2009;Srivastava 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the effect of these inter-personal relationships with individuals, employees' turnover intentions and behaviour are also influenced by their interactions with groups within the organisation, which are perceived holistically, and not as a collection of separate individuals: co-workers (Groysberg & Lee, 2010), work-group (Whiteoak, 2007), and management (Bélanger, Edwards, & Wright, 2003). Furthermore, employees' turnover intentions and behaviour are influenced by the organisation's interactions with employees through policies and processes (Allen, 2001;Kuvaas & Dysvik, 2010;Ng & Butts, 2009). …”
Section: The Nature Of the Research Subject (The Relationship)mentioning
confidence: 99%